Strategi Pembelajaran Pendidikan Agama Islam dalam Memberikan Motivasi Belajar Peserta Didik Berlatar Belakang Broken Home di SDN Kawunggading Cianjur - Rd. Dewi Lesnasari; Aris Adi Leksono (Universitas Palan, 2023)
An Islamic religious education educator does not just provide teaching materials in class but is more complex than that. Apart from educating and preparing students with knowledge, Islamic religious education educators are also fully responsible for encouraging student behavior, both from a psychological and character perspective. In the field of education, Islamic religious education educators greatly influence aspects of students' lives, both social, cultural and moral, to develop good motivation in students so that they can form individuals with noble morals. Therefore, to make this happen, appropriate learning strategies are needed that are able to increase student motivation. This research aims to explain the PAI learning strategy that is applied, analyzing the factors that support its success, as well as explaining the impact resulting from implementing the PAI learning strategy in an effort to increase student learning motivation at SDN Kawunggading, Cianjur. This research is a qualitative descriptive study. The data collection methods used were observation, interviews and documentation. The resulting data is then analyzed by means of data collection, data reduction, data presentation, and conclusions. The results of this research show that the PAI learning strategies implemented at SDN Kawunggading are implementing examples, implementing habits, giving advice, paying attention, giving punishment, and discussing with peers. Factors that influence the success of PAI learning strategies consist of external factors and internal factors; The implications of the PAI learning strategy implemented at SDN Kawungggading are able to have a good impact on broken home students as shown by the students' attitude of being diligent in going to school, having concern for the surrounding environment, having a good attitude towards teachers and friends, and being able to follow lessons in a conducive manner.